Study on the elemental mercury removal performance of co-pyrolyzed Cl-loading activated carbon and the formation mechanism of C-Cl functional groups. (15th August 2022) - Lv, Min; Luo, Guangqian; Zou, Renjie; Ji, Qingyu; Fang, Can; Wang, Li; Li, Xian; Yao, Hong
Graphical abstract: Highlights: Chloride was loaded on the activated carbon by the co-pyrolysis of PVC. The Cl-loading activated carbon presented good Hg 0 removal efficiency at 140 °C. The effects of NO, O2, SO2, HCl on mercury removal were investigated. There were two formation paths of C-Cl functional groups at different temperatures. Abstract: Co-pyrolysis is a convenient method to load chloride on an adsorbent to improve its mercury removal ability. However, as a main reactive species, the formation mechanism of C-Cl functional groups remained unclear. In this study, the coconut shell activated carbon (AC) was co-pyrolyzed with polyvinyl chloride (PVC) to prepare a Cl-loading activated carbon, and it presented the best mercury removal efficiency (greater than 85%) at 140 °C. NO, O2 and HCl promoted the mercury removal ability of Cl-loading activated carbon, while SO2 inhibited. By comparing the performance of Cl-loading adsorbents using different Cl sources and supporters, we found that there were two formation paths for C-Cl functional groups. The first path was that some organic chlorine in PVC was reformed at low temperature (∼300 °C), and adhered to the surface of the adsorbent in the form of C-Cl functional groups. As the co-pyrolysis temperature increased, unstable C-Cl functional groups were decomposed and the mercury removal ability became weak. The second path was that the Cl first released out from PVC as gaseous HCl, and then combined with newly exposed carbon atom sites, which were generated owing to the devolatilization process of AC at high temperature (∼800 °C), to form C-Cl functional groups for mercury removal.